(untitled) (Journal of the College of Basic Education, 2026)
The importance of the study lies in searching for (the intellectual and scientific role of Abbas bin Ali, peace be upon him), and this aspect is worthy of study and attention, especially since libraries are scarce in searching for the history of this great Imam, as She focused her attention on researching wicked figures, while marginalizing the righteous and great figures who had a significant impact in changing the behavior of many people for the better and more complete. As for our choice of this topic, it is due to the status of Abu al-Fadl al-Abbas and his heroic role in the Battle of Karbala. This role reflected his thought and knowledge. To fill the gap in studies on his scientific heritage, researchers have neglected to mention his intellectual and scientific role, forgetting that his thought